2012
DOI: 10.1007/s11046-012-9566-3
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Study of Species Distribution and Antifungal Susceptibilities of Candida Bloodstream Isolates at a Brazilian Tertiary Hospital

Abstract: To describe the incidence and susceptibility profile of Candida bloodstream infections in a tertiary-care hospital, we performed a retrospective observational study from 1998 to 2007. Comorbidities and risk factors were compiled from all cases. In vitro susceptibility testing to fluconazole, itraconazole, voriconazole, and amphotericin B was performed for 100 isolates, and caspofungin was tested for C. parapsilosis complex. In a ten-year evaluation of candidemias, 44 % were caused by C. albicans, and species o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
19
3
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 54 publications
6
19
3
1
Order By: Relevance
“…This is in accord with most studies from our region [12][13][14][15][16][17][18][19][20][21][22][23][24] and from different parts of the world [31,34,35], where all Candida isolates exhibited high susceptibility to amphotericin B, with MICs of up to 1 mg/L. In contrast, the majority of the isolates in our study showed high levels of resistance (35%-79%) to itraconazole.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This is in accord with most studies from our region [12][13][14][15][16][17][18][19][20][21][22][23][24] and from different parts of the world [31,34,35], where all Candida isolates exhibited high susceptibility to amphotericin B, with MICs of up to 1 mg/L. In contrast, the majority of the isolates in our study showed high levels of resistance (35%-79%) to itraconazole.…”
Section: Discussionsupporting
confidence: 92%
“…Though C. dubliniensis is known to be a causative agent of oral mucocutaneous infection, and has been described as a candidemia agent since 1999, our findings are in concordance with the reported low frequency (0.35%-3%) from different parts of the world [33,34].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations